Physical Activity in Pregnancy: A Preventive Measure Against Postpartum Depression - Jakub Sadowski; Julia Dołęga; Bartłomiej Zabawa; Małgorzata Łabuś; Karol Krzykawski; Łukasz Papież; Tomasz Maciejczyk; Antoni Sieńko; Patrycja Hudzińska; Piotr Mól (Quality in Sport)
Introduction: The aim of this study is to present current knowledge on the role of physical activity during pregnancy in reducing postpartum depression (PPD) symptoms. PPD is a widespread mental health condition, which significantly impacts maternal and neonatal well-being. Exercises during pregnancy are recognized as a preventative strategy that promotes both physical and mental health, benefiting mothers and their children.